The impact of process innovation in product design - a case study in the General Company for Electrical Industries - ayad mahmoud alrahim; donya hassan (Iraqi Journal for Administrative Sciences, 2024)
Is intense competition in global markets one of the challenges faced by organizations in various sectors. Fathvzat companies to search for new competitive advantages as to quality, flexibility and speed of delivery and cost appropriate has become despite the great importance of any plant productivity is not sufficient to achieve the objectives established for the large number of producers and the growth of information technology that have contributed a lot to offer new products or the development of production processes have contributed to support the competitiveness of the business Vatjht towards the creativity of the process. The creativity of the process is today a crucial factor in the entity's ability to survive and grow, and develop new processes or improve existing processes become contexts adopted by most of the facilities and seeks to invest in the design of a product satisfies a need and desire of the customer and meets the requirements of multi renewable. Were enrolled in four classes Find drawer of interest can be President for each chapter as follows: The first chapter discusses the research methodology through the presentation of the problem and the goals and the importance of the study and outline of the study and identification of a site study and methods of data collection and statistical methods used. The second chapter presents the theoretical side, first and second displays creativity creativity process and intervention types and factors affecting it and its goals and third product, design and design principles and steps of the process of designing the product. Chapter III respect to the side of the Applied Research shows the first results of the level of effectiveness of the research variables distinguished the process and product design and the second contains the reality of the research variables in the company. Third, dedicated to showcasing the analysis and discussion of the results. Chapter IV contains the conclusions and recommendations that we reached.